Tot Poenae Quot Delicta? - Tobias Fädler (University of Vienna Law Review)
In recent years, the cumulative imposition of administrative fines, as provided for under Austrian administrative criminal law, has increasingly become the focus of rulings of the Court of Justice of the European Union. In view of this development, the aim of this paper is to examine the implications of European law pertaining to the cumulative imposition of administrative fines. By analysing the relevant case law of the Court of Justice, the paper establishes how the proportionality of cumulated administrative fines is to be assessed from an EU law perspective and what particularities need to be taken into account.